Leaking capacitors muck up motherboards. - Yu-Tzu Chiu (IEEE spectrum)
Aluminum electrolytic capacitors with a low equivalent series resistance (ESR) are high-capacitance components that generally serve to smooth out the power supply to chips. Throughout 2002, they have been breaking open and failing in certain desktop PCs. So far, the only motherboard maker to admit to the problem is ABIT Computer Corp. (Taipei), and the only major PC maker to acknowledge being affected is IBM Corp. But the problem is likely to be more widespread. It is clear now that a faulty electrolyte is to blame for the burst capacitors. Apparently, a scientist stole the formula for an electrolyte from his employer in Japan and began using it himself at the Chinese branch of a Taiwanese electrolyte manufacturer. He or his colleagues then sold the formula to an electrolyte maker in Taiwan, which began producing it for Taiwanese and possibly other capacitor firms. Unfortunately, the formula as sold was incomplete.